Transfer Pricing in Cable Industry: Comparative Arm’s Length Profitability Using Tnmm Between Indonesian and Foreign Company - Andri Marfiana; Endah Sitarasmi; Sakti Prabowo; Sandika Ilham Muhammad (Ilomata International Journal of Tax and Accounting, 2026)
FThis study evaluates arm’s length profitability in the Indonesian cable industry by comparing the Return on Sales (ROS) of listed companies with independent foreign comparables using a Transactional Net Margin Method (TNMM) framework. Although the OECD Transfer Pricing Guidelines and Indonesia’s Minister of Finance Regulation Number 172 of 2023 provide a normative basis for comparability analysis, empirical evidence at the industry level remains limited. This study addresses this gap by applying a cross-jurisdictional comparability design within a capital-intensive manufacturing context, explicitly linking regulatory guidance with firm-level profitability assessment. The research adopts a descriptive-comparative approach using secondary financial data from Indonesian listed cable companies and independent foreign comparables identified through the ORBIS database. The results show that some companies fall within the interquartile range of comparable firms, while others deviate above or below the range, reflecting differences in operational performance, cost structures, and market conditions across firms and periods. These findings provide an empirical basis for assessing relative profitability positions; however, they should be interpreted as indicative rather than definitive evidence of compliance, given the reliance on external comparables and profitability-based testing. Overall, the study demonstrates that TNMM with ROS is analytically useful for evaluating profitability comparability in this context, while emphasizing the need for contextual interpretation beyond mechanical application of comparability criteria.